Asymmetric Aldol Reaction of α‐Acetoxyimino Aldehydes and its Application in the Synthesis of Substituted 1, 2‐Oxazine Derivatives. Issue 14 (10th September 2014) - Yasui, Yusuke; Ogata, Kento; Sato, Itaru; Hayashi, Yujiro
Abstract We have developed an asymmetric cross‐aldol reaction of α‐acetoxyimino aldehydes with aldehyde pro‐nucleophiles, catalyzed by proline, to afford γ‐acetoxyimino‐β‐hydroxy aldehydes in good yield with excellent enantioselectivity. The obtained aldol products have been successfully converted to 1, 2‐oxazines with four contiguous chiral centers in excellent diastereoselectivity in one‐pot via sequential reactions such as deacetylation, oxy‐Michael reaction and reduction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>